2015
DOI: 10.1002/ange.201507122
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent Synthesis of N‐Heterocycles by Catalyst‐Controlled, Activity‐Directed Tandem Annulation of Diazo Compounds with Amino Alkynes

Abstract: A stereodivergent synthesis of five‐membered N‐heterocycles, such as 2,3‐dihydropyrroles, and 2‐methylene and 3‐methylene pyrrolidines, has been developed through a tandem annulation of amino alkynes with diazo compounds and involves the trapping of in situ formed intermediates. Mechanistic investigations indicate that the copper‐catalyzed tandem annulations proceed by allenoate formation and subsequent intramolecular hydroamination. In contrast, the rhodium‐catalyzed protocol features a carbenoid insertion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Recent studies have shown that AgOTf-catalyzed dehydrative cycloisomerization proceeding through the tandem hydroamina-tion/hydroarylation steps of substituted 2-alkynonanilines 305 is an efficient method for constructing spirofused indene-indolinones 306 (Scheme 81). [292] A well-established approach to the synthesis of Nheterocycles using tandem annulation of diazo compounds with amino alkynes [293] was also distributed to obtain spiro derivatives of indole or other heterocycles. So, 2-ethynylanilines 307 react with Meldrum's acid diazo 308 in the presence of the rhodium catalyst to provide the desired product 309a or the benzyl protected compound 309b (Scheme 82).…”
Section: Synthesis Strategy For Spiro-fused Heterocycles From 2-alkynmentioning
confidence: 99%
“…Recent studies have shown that AgOTf-catalyzed dehydrative cycloisomerization proceeding through the tandem hydroamina-tion/hydroarylation steps of substituted 2-alkynonanilines 305 is an efficient method for constructing spirofused indene-indolinones 306 (Scheme 81). [292] A well-established approach to the synthesis of Nheterocycles using tandem annulation of diazo compounds with amino alkynes [293] was also distributed to obtain spiro derivatives of indole or other heterocycles. So, 2-ethynylanilines 307 react with Meldrum's acid diazo 308 in the presence of the rhodium catalyst to provide the desired product 309a or the benzyl protected compound 309b (Scheme 82).…”
Section: Synthesis Strategy For Spiro-fused Heterocycles From 2-alkynmentioning
confidence: 99%
“…To the best of our knowledge,this is the first report on the formation of functionalized dienamines through carbenoids. [19,20] To explore the synthetic utility of these dienamines,w eenvisioned that an arylamine tethered electrophile (R 1 = electrophile) would enable an intramolecular cyclization to give valuable nitrogen heterocycles.Herein we report an ovel rhodium(II)/Brønsted acid and gold(I)-catalyzed [3+ +3] annulation of enaldiazo ketones with Npropargyl anilines,t hus leading to highly substituted functionalized 1,4-oxazines (Scheme 1b). These novel oxazines serve as substrates for structural diversification through the appended olefin and enal functionalities.…”
mentioning
confidence: 99%
“…[12] In 2014, as part of our fragment-oriented synthesis program, we reported the use of diazo compounds in an O-H insertion to construct the cyclization precursor for preparation of diverse 2,2-disubstituted oxetane derivatives. [14,15] Hu and Moody recently independently demonstrated N-H insertion to b-aminoketones followed by intramolecular aldol to access pyrrolidines. [14,15] Hu and Moody recently independently demonstrated N-H insertion to b-aminoketones followed by intramolecular aldol to access pyrrolidines.…”
mentioning
confidence: 99%
“…[13] In 2015, Sun cyclized homopropargylic amines with Rh and Cu carbenes to form various alkylidine pyrrolidines. [14,15] Hu and Moody recently independently demonstrated N-H insertion to b-aminoketones followed by intramolecular aldol to access pyrrolidines. [16] We envisaged using diazo compounds as astitch to form 4-,5-, 6-, and 7-membered N-heterocycles,a ll involving the same strategic disconnection.…”
mentioning
confidence: 99%